Multiple Radiologic Findings in a Simple Blunt Thoracic Trauma - Sidipratomo, Prijo; Pandelaki, Jacob; Widjaja, Samuel; Jason, Jason (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Blunt thoracic trauma is one of the main contributors to trauma-related deaths, with the broad possibility of pathological chest injury. Imaging plays an important role in detecting most of internal organ injuries. Here we presented a 56-years-old male with progressive chest pain following blunt chest trauma several days prior without any early intervention. Chest radiograph showed rib fractures, pneumothorax, atelectasis, and raised left hemidiaphragm. Further CT scan evaluation identified additional hemothorax, subcutaneous emphysema and confirming the fourth to tenth rib fractures, pneumothorax, and unilateral hemidiaphragm elevation. As seen in our case, chest radiograph is crucial in initial evaluation of chest injury, usually through identification of pathological landmark. While chest radiograph is limited to one projection, CT scan provide a global evaluation of a region with a high sensitivity and specificity in detecting and confirming most of the injuries. Thus, one must not overlook any lightly appeared blunt thoracic trauma while optimizing the use of radiography and CT scan for the evaluation of injuries.